PATHOMORPHOSIS OF FOCAL EPILEPSY AND ITS NEUROPHYSIOLOGICAL CORRELATES - N. A. Sivakova; E. A. Korsakova; L. V. Lipatova (Эпилепсия и пароксизмальные состояния, 2018)
The specific EEG patterns in patients with epilepsy enable the objective assessment of changes in the brain function and, in conjunction with clinical data, determine the efficacy of treatment. Characteristics of the EEG spectral power have additional diagnostic values as they reflect the severity and spatial distribution of epileptiform activity. The standard EEG analysis combined with further mathematical processing helps reveal the neurophysiological markers of resistance to anti-epileptic drugs.The aim is to identify the neurophysiological correlates of drug-resistance.Materials and methods. We examined 160 patients with epilepsy: 80 with drug-resistant epilepsy (DRE) and 80 with controlled epilepsy (CE). The subjects underwent a number of neurophysiological studies (EEG, EEG-video monitoring) including the spectral power analysis.Results. We established a correlation between the paroxysmal activity localization and drug-resistance. The secondary bilateral synchronization syndrome of different degrees of severity was found in the DRE group 1.91 times more often than in the CE group; this syndrome is seen as an unfavorable factor aggravating the course of epilepsy in the DRE patients. Using the spectral analysis we also found that patients with DRE differed from those with CE by the types of paroxysmal activity in the frontal-occipital areas. There, the involvement of diencephalic and mesencephalic structures in the paroxysms were similar in the DRE group, while only diencephalic structures played a significant role in the paroxysmal activity in CE patients.Conclusion. Neurophysiological factors correlating with resistance to antiepileptic drugs in patients with epilepsy were identified. The results can be used for the timely diagnosis of pathomorphism of epilepsy and the choice of therapy.